General Anesthesia in Red-footed Tortoise (Chelonoides carbonaria) for Gastric Foreign Body Removal - Siepmann, Ellen Cristina; Sinotti, Jéssica Fernanda; Fucks de Souza, Carolina; Nishimura, Hidemi Kelly; Tanabe, Larissa Yurika; Piccoli, Ronaldo José; da Cunha, Olicies; Fukushima, Fabiola Bono (Acta Scientiae Veterinariae, 2021)
Background: The anatomical, physiological, and pharmacological characteristics of reptiles make anesthesia in chelonians particularly challenging. Specific literature regarding safe anesthetic protocols that provide immobilization, antinociception, amnesia, and unconsciousness are scarce. Thus, this paper aims to report the case of a red-footed tortoise submitted to long-duration general anesthesia to celiotomy for foreign body removal. Case: An adult red-footed tortoise (Chelonoides carbonaria), 5.9 kg, was admitted due to hyporexia after ingesting a metallic fishhook. Serial radiographs confirmed the diagnosis and location of the foreign body in the stomach. The animal was premedicated with 0.03 mg/kg dexmedetomidine, 6 mg/kg ketamine, and 0.4 mg/kg butorphanol intramuscularly. After 90 min we inserted a 22G jugular catheter and proceeded to anesthesia induction with 5 mg/kg propofol. We intubated the animal with a 2.5 mm uncuffed endotracheal and started fluid therapy at a rate of 5 mL/kg/h. Surgical anesthesia was maintained with isoflurane in 0.21 oxygen, in a non-rebreathing circuit (baraka), under spontaneous breathing. Expired isoflurane was maintained between 3 and 4.5%. Due to reduced respiratory rate and hypercapnia, we opted for implementing manually-assisted positive pressure ventilation. Morphine (0.5 mg/kg) was administered at 10 and 87 min after the beginning of the surgery for further analgesia when the isoflurane requirement increased significantly. We did not detect any alterations in heart and body temperature. Surgical anesthesia lasted 6 h. During anesthesia recovery, voluntary head retraction and coordinated movement of the limbs occurred at 240 and 540 min after the extubation, respectively. In 2 days, the patient returned to voluntary feeding, being very active and responsive to stimulus. The post-surgical hematologic evaluation was unremarkable. Discussion: Pre-anesthetic medication aimed to promote sedation and preemptive analgesia. Due to its minimal cardiorespiratory depression, we chose the combination of ketamine, dexmedetomidine, and butorphanol. Dexmedetomidine reduced the ketamine dose and caused sufficient muscle relaxation and immobilization to perform the jugular catheter placement. Butorphanol is an agonist-antagonist opioid; that is why we decided to add it to the protocol for antinociception. However, due to signs of nociceptive response (increased isoflurane requirements and heart rate), and considering the evidence of a predominance of μ receptors in reptiles, we administered low-dose morphine twice during the procedure. Propofol was chosen as an induction agent at a dose sufficient to allow endotracheal intubation. Since reptilians often show apnea in the presence of 100% oxygen, we used a 0.21 oxygen fraction. Despite this, the patient showed respiratory depression. Due to right to left cardiac shunt, sudden changes in the direction of the blood can lead to very rapid changes in the serum concentrations of isoflurane, which leads to frequent oscillations in the anesthetic depth and consequently the need for vaporizer adjustments, which may justify the high expired isoflurane fraction during the procedure. Despite that, physiological parameters were maintained within normal ranges for the species, with slight variations during the surgical procedure. We conclude that the proposed anesthetic protocol is safe for long-duration anesthesia in chelonians, ensuring cardiovascular and respiratory stability. Thus, this report may help veterinarians to perform safe anesthesia in tortoises submitted to invasive surgical procedures. Keywords: testudines, dexmedetomidine, ketamine, butorphanol. Descritores: testudines, dexmedetomidina, cetamina, butorfanol.